Up-regulated long non-coding RNA ILF3-AS1 indicates poor prognosis of nasopharyngeal carcinoma and promoted cell metastasis. Issue 4 (December 2020) - Yang, Xuewen; Lin, Feng; Gao, Feng
Background: Long non-coding RNAs (lncRNAs) have been confirmed to participate in the regulation of nasopharyngeal carcinoma. Here, we endeavored to explore the character of lncRNA ILF3-AS1 in the nasopharyngeal carcinoma and its function. Methods: A total of 68 nasopharyngeal carcinoma tissues and adjacent normal nasopharyngeal tissues were collected. Expressions of lncRNA ILF3-AS1 in these tissues were detected using quantitative real-time polymerase chain reaction (qRT-PCR). The relationship between the expression level of lncRNA ILF3-AS1 and clinical pathological characteristics was analyzed. Inhibition of lncRNA ILF3-AS1 was done using small interference RNA. Results: lncRNA ILF3-AS1 expression was significantly up-regulated in the 68 nasopharyngeal carcinoma tissue samples compared to their adjacent normal tissue samples. Increased lncRNA ILF3-AS1 level was related to the advanced tumor node metastasis stage and the metastasis of nasopharyngeal carcinoma. Also, increased lncRNA ILF3-AS1 indicated poor prognosis of nasopharyngeal carcinoma patients. Inhibition of lncRNA ILF3-AS1 reduced proliferation, invasion and migration of nasopharyngeal carcinoma cells. MicroRNA-320a (miR-320a) was determined as a direct target for lncRNA ILF3-AS1 in nasopharyngeal carcinoma. Furthermore, lncRNA ILF3-AS1 could sponge miR-320a to promote BMI1 expression. The expression of BMI1 was significantly inhibited by the down-regulation of lncRNA ILF3-AS1. Conclusions: For the first time, we demonstrated that lncRNA ILF3-AS1 was markedly over-expressed in nasopharyngeal carcinoma tissues and cells. Elevated lncRNA ILF3-AS1 expression was correlated with severe cancer stage and poor prognosis. lncRNA ILF3-AS1 could promote proliferation, invasion, and migration of cells, which might indicate a novel target site for the future diagnosis and therapy of nasopharyngeal carcinoma.